Efektivitas Program Kredit Usaha Rakyat di PT Bank Sulselbar terhadap Pendapatan UMKM di Kabupaten Sidenreng Rappang - Nurul Ainun Salsabila; Pratiwi Ramlan; Haslindah; Muhammad Rusdi (Jurnal Paradigma Ekonomika, 2025)
Micro, small, and medium enterprises play a strategic role in driving regional economic growth, yet they still face challenges in accessing capital. The government, through PT Bank Sulselbar, distributes the People's Business Credit program as an effort to increase the income of business actors. This study aims to determine the effectiveness of the People's Business Credit program on increasing the income of micro, small, and medium enterprises in Sidenreng Rappang Regency. The research uses a descriptive quantitative approach with survey techniques through questionnaires distributed to 68 respondents. Data analysis was conducted using validity tests, reliability tests, normality tests, multiple linear regression, and hypothesis testing. The results show that input and process variables have a positive and significant effect on income increase, with a contribution rate of 68.1 percent. This study concludes that the People's Business Credit program is effective in supporting business development and increasing the income of small business actors in the region.